Statin myopathy: the fly in the ointment for the prevention of cardiovascular disease in the 21st century?. (September 2014) - Keen, Helen I; Krishnarajah, Janakan; Bates, Timothy R; Watts, Gerald F
<x xml:space="preserve">Abstract</x> Introduction: Cardiovascular disease (CVD) remains the leading cause of death in industrialized nations. Despite clear evidence of CVD risk reduction with HMG-CoA reductase inhibitors (statins), the side effects of these medications, particularly myopathy, limit their effectiveness. Studies into the mechanisms, aetiology and management of statin myopathy are limited by lack of an internationally agreed clinical definition and tools for assessing outcomes. Currently there is a paucity of evidence to guide the management of patients affected by statin myopathy; with the exception of dose reduction, there is little evidence that other strategies can improve statin tolerance, and even less evidence to suggest these alternate dosing strategies reduce cardiovascular risk. Areas covered: This review will cover current definitions, clinical presentations, risk factors, pathogenesis and management. PubMed was searched (English language, to 2014) for key articles pertaining to statin myopathy. This review then briefly describes our experience of managing this condition in a tertiary lipid disorders clinic, in the setting of limited guiding evidence. Expert opinion: Knowledge gaps in the field of statin myopathy are identified and future research directions are suggested. We urge the need for international attention to address this important, but largely neglected clinical problem, that if unresolved will remain an impediment to the effective prevention and treatment of CVD.